PENGARUH OPINI AUDIT, GOING CONCERN, DAN PROFITABILITAS PERUSAHAAN PADA AUDITOR SWITCHING DENGAN FINANCIAL DISTRESS SEBAGAI VARIABEL MODERASI (Studi Empiris pada Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia Tahun 2013-2016) - Widya Elisa; Hardi Hardi; Ilham Elfi (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2019)
To produce reliable financial reports, the client company is required toconduct audit rotation. The obligation of auditor rotation in Indonesia isregulated by the Indonesian government in the Regulation of the Minister ofFinance of the Republic of Indonesia Number 17 / PMK.01 / 2008 concerning"Public Accountant Services". The purpose of this study was to determine theeffect of audit opinion, going concern, and company profitability on auditorswitching with financial distress as a moderating variable in manufacturingcompanies listed on the IDX. The samples in the study were 25 companiesconducted by purposive sampling technique. The research method used isdescriptive analysis method using logistic regression analysis and data analysisused, namely the Moderated Regression Analysis (MRA) test. The results obtainedby the audit opinion, company profitability and financial distress has a partiallysignificant effect on auditor switching. But the going concern variable does not aeffect partially significant effect on auditor switching, and the moderatingfinancial distress variable is able to moderate audit opinion and companyprofitability on auditor switching, but the moderating financial distress variable isnot able to moderate the going concern towards the auditor switching.Keywords : audit opinion, going concern, company profitability, financialdistress, auditor switching.